How Does the Unique Space‐Time Sampling of the SWOT Mission Influence River Discharge Series Characteristics?. Issue 14 (29th July 2019) - Nickles, Cassandra; Beighley, Edward; Zhao, Yuanhao; Durand, Michael; David, Cedric; Lee, Hyongki
Abstract: The Surface Water and Ocean Topography (SWOT) satellite mission will, for the first time, provide simultaneous, high‐resolution measurements of water surface elevation and extent. Here we explore the applicability of SWOT's unique sampling to capture discharge frequency behavior throughout the Mississippi River Basin. Our findings suggest the mission may capture key variability in river discharge series. SWOT orbit specifications, US Geological Survey (USGS) discharge measurements, and potential uncertainty estimates are used to generate SWOT‐like river discharges. Frequency distributions and specific quantiles derived from synthetic SWOT discharge series are compared to those derived from daily USGS discharge series. Based on the Kolmogorov‐Smirnov test, SWOT temporal sampling has essentially no impact on derived frequency distributions. When including potential uncertainty, 78% of derived distributions are statistically identical. The combined effects of temporal sampling and discharge uncertainty mitigates the negative bias used for SWOT discharge uncertainty at larger discharge quantiles (i.e., ≥75% quantiles). Plain Language Summary: The Surface Water and Ocean Topography (SWOT) satellite will, for the first time, simultaneously measure elevations and extents of the Earth's surface waters at high resolution. The satellite will measure almost everywhere on Earth as many as seven times every 21 days, with more observations at higher latitudes. In this study, we explored how nonuniform measurements in time, varying by location, impact the ability of SWOT to capture river discharge frequency behavior. Based on the comparison between discharge frequency distributions derived from daily USGS gauge measurements and synthetic SWOT observations, SWOT's unique temporal sampling does not impact observed discharge behavior. When considering both temporal sampling and uncertainty, 78% of the study locations still match the truth discharge frequency distributions. In general, SWOT temporal sampling has minimal impact on derived discharge quantiles, but the combination of both temporal sampling and uncertainty leads to underestimated discharge quantiles. The magnitude of the underestimated discharges for larger quantiles (i.e., ≥75%) is less than the negative bias used for SWOT discharge uncertainty, implying a mitigation of negative bias in discharge at larger discharge quantiles. Key Points: SWOT temporal sampling has minimal impact on derived river discharge frequency distributions throughout the Mississippi River Basin SWOT‐derived discharge distributions are statistically the same as those derived from daily in‐situ measurements in 78% of cases Quantiles derived from synthetic SWOT discharges series have RRMSE of less than 22%